Drug kinetics and antimicrobial properties of quaternary bioactive glasses 81S(81SiO2-(16-x)CaO-2P2O5-1Na2O-xMgO); an in-vitro study - Yadav A.K.; Tripathi H.; Rajput S.; Singh P.; Dubey A.K.; Kumar K.; Chawla R.; Rath C. (My University, 2025)
Bioactive glasses have recently been attracted to meet the challenge in bone tissue regeneration, repair, healing, dental implants, etc. Among the conventional bio-glasses, a novel quaternary mesoporous nano bio-glass with composition 81S(81SiO2-(16-x)CaO-2P2O5-1Na2O-xMgO) (x = 0, 1.6, 2.4, 4 and 8 mol%) employing Stober's method has been explored for examining the above potential application through in-vitro SBF assay, MTT assay, antimicrobial activity and drug loading and release ability. With increasing the MgO concentration up to 4 mol%, from in-vitro SBF assay, we observe that HAp layer develops on the surface of the nBGs confirmed from XRD, FTIR and FESEM. MTT assay using MG-63 cells confirms the biocompatibility of the nBGs having cell viability >225 % for MGO_4 after 72 h which is more than the clinically used 45S5 bio-glass. We have observed cell viability of >125 % even after 168 h. Moreover, MGO_4 is found to restrict the growth of E. coli by 65 % while S. aureus by 75 %, confirming the antimicrobial activity. Despite an increase in the concentration of magnesium, nBGs are found to be non-toxic towards the RBCs up to 4 mol% of MgO while for 8 %, the hemolysis percentage is >6 % which is toxic. Being confirmed MGO_4 nBG as a bioactive material, various concentrations of drug (Dexamethasone (DEX)) loading and release kinetics are examined. We show that 80 % of loading in case of 10 mg-ml−1 and 70 % of cumulative release in 100 h. The mesoporous structure of MGO_4 having an average pore diameter of 5 nm and surface area of 216 m2 g−1 confirmed from BET supports the loading and release kinetics. We conclude that the quaternary MGO_4 nBG may be employed effectively for bone tissue regeneration due to its high biocompatibility, excellent in-vitro cell viability, antimicrobial response and protracted drug release. © 2023